Cognitive decline in the elderly: an analysis of population heterogeneity - Hayden, Kathleen M.; Reed, Bruce R.; Manly, Jennifer J.; Tommet, Douglas; Pietrzak, Robert H.; Chelune, Gordon J.; Yang, Frances M.; Revell, Andrew J.; Bennett, David A.; Jones, Richard N. (Age and ageing, 2011)
Background: studies of cognitive ageing at the group level suggest that age is associated with cognitive decline; however, there may be individual differences such that not all older adults will experience cognitive decline. Objective: to evaluate patterns of cognitive decline in a cohort of older adults initially free of dementia. Design, setting and subjects: elderly Catholic clergy members participating in the Religious Orders Study were followed for up to 15 years. Cognitive performance was assessed annually. Methods: performance on a composite global measure of cognition was analysed using random effects models for baseline performance and change over time. A profile mixture component was used to identify subgroups with different cognitive trajectories over the study period. Results: from a sample of 1,049 participants (mean age 75 years), three subgroups were identified based on the distribution of baseline performance and change over time. The majority (65%) of participants belonged to a slow decline class that did not experience substantial cognitive decline over the observation period [−0.04 baseline total sample standard deviation (SD) units/year]. About 27% experienced moderate decline (−0.19 SD/year), and 8% belonged to a class experiencing rapid decline (−0.57 SD/year). A subsample analysis revealed that when substantial cognitive decline does occur, the magnitude and rate of decline is correlated with neuropathological processes. Conclusions: in this sample, the most common pattern of cognitive decline is extremely slow, perceptible on a time scale measured by decades, not years. While in need of cross validation, these findings suggest that cognitive changes associated with ageing may be minimal and emphasise the importance of understanding the full range of age-related pathologies that may diminish brain function.